Political Economy of Antidumping and Safeguards in Argentina - Nogués, Julio J.; Baracat, Elías (World Bank, Washington, DC, 2012)
Beginning in the late 1980s, Argentina implemented a series of reforms that were revolutionary in speed and scope, including trade liberalization. After the implementation of these policies, a record number of antidumping petitions came forward. Under a situation of high inflation, the government reinforced its fiscal and monetary policies by announcing that it would minimize the use of such measures. The flexible disciplines of the existing domestic antidumping regulations facilitated this objective. Later, when the GATT/WTO-sanctioned trade remedies were implemented, the government made a serious attempt to establish discipline by including liberal regulations and creating special institutional arrangements. A presumption built into the construction of the new mechanisms was that adhering to WTO requirements would strengthen the resistance against protection. This presumption turned out to be false. Changing circumstances, including severe peso overvaluation, had significant effects on the number and outcome of antidumping investigations. Regarding safeguards, the government followed the letter and the spirit of the WTO agreement. In relation to the number of petitions, few measures have been implemented. Rejections were based on a concern for consumer costs and on failure of the industry seeking protection to provide a convincing modernization plan. This, plus the fact that some cases were brought to the WTO Dispute Settlement Body, have made safeguards a less attractive instrument for protection-seekers than antidumping. An important positive side of the story is that unlike previous balance of payments adjustments, in spite of the major crisis that followed the recent devaluation, the hard-won liberalization has been maintained.